2011
DOI: 10.7439/ijbr.v2i3.93
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatoprotective Activity of Capparis Sepiaria Leaves

Abstract: The effect of the ethanolic extract of the leaves of capparis sepiaria Linn was studied against carbon tetrachloride induced hepatotoxicity in Wister rats. Significant hepatoprotective effects were obtained in liver damage induced by carbon tetrachloride as evident from decreased serum levels of glutamate pyruvate transaminase (SGPT),glutamate oxaloacetate transaminase (SGOT), alkaline phosphatase (ALP) and bilirubin (SB) in the capparis sepiaria (CS) treated groups (100,200 mg/kg), compared to the intoxicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Histopathological observations was further confirmed the hepatoprotective effect of CS and proved the effect of CS in preventing hepatocellular necrosis and cellular degeneration caused bt CCl 4 exposure. 118 Thus CS extract may bring the almost normal histological architecture of the liver.…”
Section: Capparis Sepiaria (Family: Capparaceae)mentioning
confidence: 98%
See 1 more Smart Citation
“…Histopathological observations was further confirmed the hepatoprotective effect of CS and proved the effect of CS in preventing hepatocellular necrosis and cellular degeneration caused bt CCl 4 exposure. 118 Thus CS extract may bring the almost normal histological architecture of the liver.…”
Section: Capparis Sepiaria (Family: Capparaceae)mentioning
confidence: 98%
“…It is claimed to be useful as diuretic, anthelmintic, antidiabetic, expectorant and hepatoprotective in traditional system of medicine. 118 Antimicrobial, cytotoxicity and anti-inflammatory activity has been reported. 119 It contains various flavanoid such as kaempferol, quercetin, isohamnetin, galactoside, flavanone glucoside pernisol, persinoside A and B.…”
Section: Aerva Lanata (Family: Amaranthaceae)mentioning
confidence: 99%
“…Capparis Spinosa L. belonging to the family, Capparidaceae is a thorny much branched shrub traditionally used for the treatment of jaundice, inflammation and dysentery (Indian Medicinal Plants, 1999;Matthew, 1991). Various parts of Capparis Spinosa has been reported to possess anti-inflammatory and analgesic actitivies (Chaudhari et al, 2004) and, hepatoprotective activity (Satyanarayana et al, 2009); ethanolic leaf extracts also showed significant in vitro free radical scavenging activity (Thirumalaikumaran and Reddy, 2011); stem extracts of Capparis Spinosa are reported to possess antimicrobial and anti-inflammatory activity (Satyanarayana et al, 2010). There are very scientific reports available with regard to the biological activities of Capparis Spinosa, the antibacterial activity of leaf and root extracts is scanty.…”
Section: Introductionmentioning
confidence: 99%